Endocrinology. Vol. 2 (W.B. Saunders Company. A Division of Harcourt Brace and Company, 1995)
Revised throughout, the 5th Edition of this leading reference presents a complete and up-to-date review and analysis of all aspects of endocrinology, diabetes, and bone metabolism. Readers will also find state-of-the-art information on genetics, proteinomics, and hormone signaling, and coverage of the field\'s hottest topics in nearly 20 new chapters. Joined by an international team of leading experts-many new to this edition-Drs. Jameson and DeGroot provide guidance that integrates the basic science of endocrinology with clinical medicine and the practical management of endocrine disorders. A clinical focus emphasizes diagnosis and therapy.Features the work of the world\'s leading authorities-many new to this edition.Organizes information into basic and clinical sections that makes reference quick and easy.Provides tables designed to summarize and organize information, and presents over 1,400 illustrations that clarify complex concepts. Examines the hottest topics in the field today through 19 new chapters including Endocrinology: Impact on science and medicine · Application of genomics and proteinomics to endocrinology · Genetic syndromes in endocrinology · Genetics and syndromes of obesity · Role of the adipocyte in metabolism and endocrine function · Genetic Defects and Disorders of Bone · and Adrenal causes of hypercortisolism.Features many new authors, offering fresh perspectives.
Keywords: Sex Differentiation; diabetes mellitus; Langerhansovy ostrůvky; paratyreoidea; Islets of Langerhans; Diabetes Mellitus; Adrenal Cortex; sexuální diferenciace; Parathyroid Glands; endokrinologie; Endocrinology; vnitřní lékařství; kůra nadledvin